2003
DOI: 10.1002/cbic.200300708
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide‐Based Knockdown Technologies: Antisense Versus RNA Interference

Abstract: The postgenomic era is characterized by an almost intimidating amount of information regarding the sequences and expression of previously unknown genes. In response, researchers have developed an increasing interest in functional studies. At the start of such a study, one may have little more than sequence information and bioinformatic annotation. The next step is to hypothesize a potential role in the context of a cell. Testing of the hypothesis needs to be fast, cheap, and applicable to a large number of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…siRNA is a more promising and advantageous strategy. Several studies have indicated that RNAi is more potent than antisense oligonucleotides even in cases where site selection was optimized for antisense effectiveness 29. One of the potential advantages of RNAi technologies is the ability to design precisely targeted therapeutics for almost any gene, regardless of the function of the gene product, whether that function is clearly defined, and in the absence of protein structure information 30.…”
Section: Discussionmentioning
confidence: 99%
“…siRNA is a more promising and advantageous strategy. Several studies have indicated that RNAi is more potent than antisense oligonucleotides even in cases where site selection was optimized for antisense effectiveness 29. One of the potential advantages of RNAi technologies is the ability to design precisely targeted therapeutics for almost any gene, regardless of the function of the gene product, whether that function is clearly defined, and in the absence of protein structure information 30.…”
Section: Discussionmentioning
confidence: 99%
“…An additional obstacle in exploring siRNA as a therapeutic tool is toxicity. siRNA have the potential to induce a concentration-and cell-type-dependent cell death [105] . In mammalian cells, the utility of RNAi has been limited by the innate immune response triggered by dsRNA.…”
Section: Questions To the Safety And Efficacy Of Using Rnai As A Thermentioning
confidence: 99%
“…Long dsRNA induce an interferon response usually resulting in a generalized inhibition of gene expression. However, this response can usually be avoided in mammalian cell cultures by using synthetic siRNA with a length of 21 nt [105] . Inhibition of viral replication by RNAi has been demonstrated in vitro for a variety of viruses, including RNA viruses such as HIV, respiratory syncytial virus, influenza virus, poliovirus, West Nile virus, dengue virus, and foot and mouth disease virus.…”
Section: Questions To the Safety And Efficacy Of Using Rnai As A Thermentioning
confidence: 99%
“…activity is considered as successful knockdown (25). Moreover, the level of silencing depends to a great extent on which region of the mRNA is targeted (26).…”
mentioning
confidence: 99%